Admixture mapping - McKeigue, Paul (Henry Stewart Talks, 2007)
Applications of statistical modelling of population admixture, Genetic and environmental explanations for ethnic differences in disease risk, Methods for finding genes that influence complex traits, Exploiting admixture to map genes, Statistical power of admixture mapping, Advantages of admixture mapping in comparison with other approaches to finding disease susceptibility genes, Methodological problems of extending linkage analysis of a cross to admixed human populations, Statistical methods that allow linkage analysis of a cross to be extended to admixed humans, Model for stochastic variation of ancestry on chromosomes inherited from an admixed parent, Multipoint inference of ancestry at marker loci from genotypes, Null hypothesis as graphical model, Statistical approach to model fitting and hypothesis testing, The score test algorithm, Other model diagnostics: "Bayesian p-values", How many markers are required for genome-wide admixture mapping?, Panels of ancestry-informative markers, Other applications of statistical modelling of admixture